Quinic acid alleviates high-fat diet-induced neuroinflammation by inhibiting DR3/IKK/NF-κB signaling via gut microbial tryptophan metabolites - Sen Li; Yuwei Cai; Tong Guan; Yu Zhang; Kai Huang; Ze Zhang; Wangqing Cao; Xiao Guan (Gut Microbes, 2024)
With the increasing of aging population and the consumption of high-fat diets (HFD), the incidence of Alzheimer’s disease (AD) has skyrocketed. Natural antioxidants show promising potential in the prevention of AD, as oxidative stress and neuroinflammation are two hallmarks of AD pathogenesis. Here, we showed that quinic acid (QA), a polyphenol derived from millet, significantly decreased HFD-induced brain oxidative stress and neuroinflammation and the levels of Aβ and p-Tau. Examination of gut microbiota suggested the improvement of the composition of gut microbiota in HFD mice after QA treatment. Metabolomic analysis showed significant increase of gut microbial tryptophan metabolites indole-3-acetic acid (IAA) and kynurenic acid (KYNA) by QA. In addition, IAA and KYNA showed negative correlation with pro-inflammatory factors and AD indicators. Further experiments on HFD mice proved that IAA and KYNA could reproduce the effects of QA that suppress brain oxidative stress and inflammation and decrease the levels of of Aβ and p-Tau. Transcriptomics analysis of brain after IAA administration revealed the inhibition of DR3/IKK/NF-κB signaling pathway by IAA. In conclusion, this study demonstrated that QA could counteract HFD-induced brain oxidative stress and neuroinflammation by regulating inflammatory DR3/IKK/NF-κB signaling pathway via gut microbial tryptophan metabolites.